Revealing the flavor differences of Sauvignon Blanc wines fermented in different oak barrels and stainless-steel tanks through GC-MS, GC-IMS, electronic, and artificial sensory analyses - Taoxian Zhang; Zusong Liao; Zhaohui Li; Yunqi Liu; Jingying Bi; Yanlin Liu; Yuyang Song; Yi Qin (Food Chemistry: X)
The fermentation vessel significantly impacts the flavor characteristics of white wine. This study provides a comprehensive flavor analysis of Sauvignon Blanc wines fermented in oak barrels and stainless-steel tanks. Wines fermented in new barrels exhibited higher levels of malic and tartaric acids compared with those fermented in old barrels or steel tanks, resulting in a more sour taste. Fermentation in oak barrels increased the content of majority phenolic compounds in wine compared to fermentation in steel tanks. GC–MS analysis revealed that the primary differential compounds present in the wines from various oak barrels and steel tanks included ethyl acetate, ethyl lactate, furfural, ethyl octanoate, isoamyl alcohol, isobutyl alcohol, 1-propanol, and acetic acid. Moreover, GC-IMS identified furan, pyrazine, acetaldehyde, and valeraldehyde in wines from oak barrels, which enhanced aromatic complexity. This study provides essential insights to promote the quality and distinctiveness of Sauvignon Blanc wines.